Geological history plants dominated the net accumulation of coal - Yanqiang SHI; Yakun SHI (Meitan kexue jishu)
In order to explore the large-scale pure accumulation mechanism of thick coal seams, reflect on the main controlling factors of coal accumulation, and study the evolution and replacement of geological history plants and their effect, the historical comparison method was applied to deduce that the coal accumulation period was formed when plants in each period developed to the peak stage, and plants in the coal accumulation period had strong colonization ability and significant group effect, occupying the dominant position of coal accumulation. Confined by the vegetation during the coal accumulation period, the clasts in the basin can only move periodically in a limited space, forming a long clastic depletion period and a short clastic explosion period. During the debris depletion period, the sea / lake beach is fully flattened, the basement environment is “abandoned”, the water body is clear, the vegetation is dense, and the peat marshes are widely distributed. The basin fluid has become the water source of in-situ coal accumulation and the carrier of coal accumulation in different places, and pure coal can be accumulated near the syngenetic debris. With the advance and retreat of sea / lake water, peat bogs can expand across different basement environments, and even extend to the whole coal accumulation basin, improve environmental hydrology, raise groundwater level, and further change the regional climate. Dynamic peat bogs are superimposed in situ in multiple layers, forming thick coal layers in favorable sections; In the net environment constructed by vegetation, some plants and peat migrate to the sea / Lake in different places and accumulate ultra thick coal seams in the marsh lake. Coordinated transformation of in-situ coal accumulation and remote coal accumulation, sustainable development in a virtuous cycle, and the formation of a dynamic coal accumulation model of cyclic net accumulation. Vegetation prevents the input of detritus. The clear water body during transgression is conducive to the development of marine peat and the formation of carbonate rocks, replacing the terrigenous detritus deposition of transgressive sequence, forming the sea land interaction “Yoredale” cycle in which limestone and coal seams are in direct contact. During the clastic explosion period, the terrigenous clastic reservoir collapsed, some clasts rushed to the edge of the peat swamp to form rock and coal interbedding, and some were transported by peat rafts into the peat swamp to deposit intermittently, forming large sedimentary breccia scattered in the coal, while a large number of clasts were transported to the sea / lake delta by the swamp river. The plant action in the process of coal accumulation can reasonably explain some “abnormal” phenomena in coal geology and fill the blank of coal geology research.